Entrapment of focal atrial tachycardia using cryoballoon ablation; Sinus rhythm in the left atrium and ongoing atrial tachycardia in the left atrial appendage - Yorgun, Hikmet (Indian Pacing Electrophysiol J, 2017)
Left atrial appendage (LAA) is a well-known source of focal atrial tachycardias (AT). Although radio-frequency (RF) energy is the most commonly used technique in such cases, there was an option other than epicardial approach when RF technique fails. Cryoballoon technology is primarily developed to be used for pulmonary vein isolation (PVI). Also, there was no report regarding the isolation of LAA by using cryo-balloon in patients with focal AT. In this case, for the first time in the literature, we successfully isolated the LAA because of failed attempts of RF ablation for focal AT in whom the surface electrogram showed a sinus rhythm while arrhythmia continues inside the LAA.